Intriguing kagome topological materials - Qi Wang; Hechang Lei; Yanpeng Qi; Claudia Felser (npj Quantum Materials)
Abstract Topological quantum materials with kagome lattice have become the emerging frontier in the context of condensed matter physics. Kagome lattice harbors strong magnetic frustration and topological electronic states generated by the unique geometric configuration. Kagome lattice has the peculiar advantages in the aspects of magnetism, topology as well as strong correlation when the spin, charge, or orbit degrees of free is introduced, and providing a promising platform for investigating the entangled interactions among them. In this paper, we will systematically introduce the research progress on the kagome topological materials and give a perspective in the framework of the potential future development directions in this field.